Casimir energy in multiply connected static hyperbolic universes - Muller, D.; Fagundes, H. V.; Opher, R. (American Physical Soc, 2002)
We generalize a previously obtained result for the case of a few other static hyperbolic universes with manifolds of nontrivial topology as spatial sections.